Breaking the Spirit of Poverty in African Pentecostal Christianity: A Traction or A Wither? - Ng’etich, Elias K. (Journal of Religion in Africa, 2023)
Abstract Poverty is one of Africa’s most intractable problems. Decades of deliberate and strategic socioeconomic policies have not yielded considerable concrete results to eradicate it. Upon succeeding the brutal colonial administration, the burgeoning African governments promised their citizens material well-being through socioeconomic development. A half century later the continent is perpetually witnessing a blatant betrayal of dreams. Just like the African governments that succeeded colonial governments, religious organizations continue to promise poverty eradication by divine means to their adherents, whose numbers keep exploding across the continent. The Pentecostal variant of African Christianity is particularly renowned for its promises of wealth, health, and prosperity through supernatural divine power: in the Bible, God has promised to deliver immense material goods to those who believe in Jesus Christ. The expediency of these promises to alleviate poverty and bring about social transformation is debatable. Some scholars argue that African Pentecostalism is an elaborately complex increase in religious activities devoid of social structural transformation, while others opine that it contributes positively to development. In asking whether African Pentecostal Christianity is a move toward or a distraction from development, this article broadly explores discourses on Pentecostalism and development in Africa. Arguably, in the endeavor to preach and live out the experiential power of the Holy Spirit, Pentecostal Christianity in Africa inadvertently plays a role in the broader ongoing development discourse. Although they do not view themselves as ‘religious’ or ‘religion’, Pentecostal churches’ attempts to make the teachings of Jesus Christ relevant to the mundane help individual believers cope with life’s stresses and vulnerabilities. However, it does not transform the social conditions that create problems for individuals. The liberating hope of African Pentecostal Christianity lies in theologically nuancing its discourses to meaningfully engage in global development discourses.
free
Keywords: development; discourses; pentecostalism; poverty; sermons